Preliminary Investigation on the Insect Pests of Cashew Plantations in Kerala - Choudhuri, J. C. Basu (Indian Forester, 1962)
The observations reported here pertain to the preliminary insect survey made in extenive cashew plantations raised under forest conditions. The problems of insect pests apd their control in these forest plantations are recent origin. Four important and potential pests species were observed and reported. Suggestions for possible chemical control measures and lines for future work are indicated.